Experimental and numerical investigation on the aging behavior of CFZnL composites in salt spray environment - Huang, J.; Liu, Y.; Hou, Y.; Yang, K.; Shi, J.; Meng, L.; Sapanathan, Thaneshan (2025)
This study develops a class of novel carbon-fiber-Zinc-alloy-laminated (CFZnL) composites, and investigates the modulus after salt spray aging. Experimental salt spray aging and tensile tests have been sequentially performed on CFZnL composites and conventional CFRP composites, to assess the aging behavior and residual tensile modulus. It has been observed that Zn alloy layer significantly enhances the aging-resistance due to moisture absorption. In addition, a multiscale modeling approach is proposed to predict the aging behavior and moduli of CFZnL and CFRP composites. Microscale models have been established to obtain the effective diffusion coefficients and effective properties of CFRP layers. Moreover, residual properties of CFRP and Zn alloy layers are calculated using an exponential degradation model. Then, they are introduced in the macroscale model for the tensile simulation. The numerical results concur well with the experimental ones, validating the accuracy of the multiscale modeling approach. It indicates that CFZnL composites with double-side Zn alloy layers possess superior aging-resistance than others in salt spray environment. Finally, the damage mechanisms are analyzed for the aged CFRP and CFZnL composites via experimental observations.